Development of Hand Hygiene Monitoring System Based on Android Mobile Application and User Perspective - Gavin Pratama Nugraha; Arlina Dewi; Nurdiansyah Ramadhan (Universitas Muhammadiyah Yogyakarta, 2023)
Hand hygiene plays a crucial role in promoting overall health and preventing the spread of diseases. The World Health Organization reported that the prevalence of healthcare-associated infections (HAIs) ranges from 3-12% in high-income countries and 5-19% in low-and middle-income countries. Improved hand hygiene compliance can substantially reduce HAI rates. In Indonesia, the Ministry of Health has designated handwashing compliance as a compulsory quality indicator for hospitals. Introducing a mobile app can improve hand hygiene practices. This study aims to develop and design an Android mobile application that serves as an easy-to-operate hand hygiene monitoring system and to understand user perspectives. The study used Agile Methods for app development and a qualitative approach to know users' perspectives. Respondents (n=10) from AMC Muhammadiyah Hospital, including the IPC team, department heads, and administrators, were interviewed. The result revealed that mobile application is easy to use and have an attractive user interface. Users expressed the application's user-friendliness and utility in conducting observations. Nonetheless, they identified some drawbacks, such as lagging issues and a complicated manual installation process due to the app's unavailability on Playstore. Users expect the app's future inclusion on Play Store for simplified installation and request its development for iOS to cater to hospital staff using iPhones.